ESG-Based Balanced Scorecard Approach in the Perspective of Green Accounting: A Literature Review on Strategic Performance of MSMEs in Sustainable Villages - Eriswanto, Elan; Indrawan, Andri; Sophan, Irfan; Rahmadini, Salva Aulia (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2026)
The growing demand for sustainable business performance measurement has encouraged the development of Green Accounting, which incorporates environmental costs into conventional financial reporting. Meanwhile, the Balanced Scorecard (BSC) remains a widely applied strategic management tool, and its integration with Environmental, Social, and Governance (ESG) indicators has resulted in the Sustainability Balanced Scorecard. This study aims to conceptualize an ESG-based Balanced Scorecard grounded in Green Accounting principles, specifically designed to address the strategic performance needs of micro, small, and medium enterprises (MSMEs) in sustainable villages. Employing a qualitative literature review, this research synthesizes academic studies, policy documents, and empirical findings published over the last decade, using thematic content analysis to identify conceptual linkages and gaps. The findings indicate that integrating ESG indicators across the four traditional BSC perspectives enables MSMEs to align financial performance with environmental responsibility and social value creation. Green Accounting provides a measurable basis for incorporating environmental costs, social contributions, and governance practices into performance evaluation. Evidence from rural MSMEs in Indonesia and other contexts shows that this integration enhances sustainability reporting, financial resilience, community trust, and access to ESG-based financing. Nevertheless, adoption remains limited due to resource constraints, lack of standardized frameworks, and differing financial impacts. The proposed ESG-BSC–Green Accounting model offers a context-specific and practical framework to support sustainable strategic competitiveness.